2021
DOI: 10.1055/a-1352-3805
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of ultrathin endoscope for esophageal endoscopic submucosal dissection

Abstract: Background and study aims Endoscopic submucosal dissection (ESD) is widely performed for superficial esophageal cancer, but stricture after extensive resection is a major clinical problem. Using an ultrathin endoscope would enable endoscopists to approach lesions beyond the stricture. We evaluated the feasibility of an ultrathin endoscope for esophageal ESD. Methods To perform ESD with an ultrathin endoscope, we developed a transparent hood and ESD knife. A total of 24 esophageal ESDs were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…An oral approach is still favored when therapy or hemostasis is likely to be required, although, as technology continues to advance and further evidence emerges [7], there is an increasing role for therapeutic TNE (such as for strictures [16], percutaneous endoscopic gastrostomy [17][18][19] and feeding tube placement [20], endoscopic submucosal dissection [21,22] and Botulinum toxin (Botox) injections [23]). Recent studies have also explored the use of uTNE in the pre-screening of bariatric surgery patients, with results suggesting that it is a well-tolerated examination and is an appropriate choice in morbidly obese patients due to minimal cardiovascular stress being induced [24,25].…”
Section: Technological Advancesmentioning
confidence: 99%
“…An oral approach is still favored when therapy or hemostasis is likely to be required, although, as technology continues to advance and further evidence emerges [7], there is an increasing role for therapeutic TNE (such as for strictures [16], percutaneous endoscopic gastrostomy [17][18][19] and feeding tube placement [20], endoscopic submucosal dissection [21,22] and Botulinum toxin (Botox) injections [23]). Recent studies have also explored the use of uTNE in the pre-screening of bariatric surgery patients, with results suggesting that it is a well-tolerated examination and is an appropriate choice in morbidly obese patients due to minimal cardiovascular stress being induced [24,25].…”
Section: Technological Advancesmentioning
confidence: 99%
“…In ESD for ESCC beyond the stricture, balloon dilation is commonly performed until a conventional endoscope may pass through. The ultrathin endoscope does not require balloon dilation, and the transparent hood mounted at the distal end of the ultrathin endoscope provides a more rapid approach to the submucosa than a conventional endoscope (1,2). Esophageal ESD with an ultrathin endoscope is a useful endoscopic treatment option for ESCC with stricture (1-3).…”
Section: Discussionmentioning
confidence: 99%
“…A novel hemostatic forceps with a 2.3 mm diameter (RAICHO, KANEKA, Osaka, Japan), suitable for the ultrathin endoscopes (FUJIFILM, Tokyo, Japan) with a 2.4 mm diameter forceps scope channel, has been made recently available in clinical practice. Several authors reported that the RAICHO was efficacious for endoscopic hemostasis during endoscopic submucosal dissection using the ultrathin endoscope [18,19]. Accordingly, the simultaneous procedure seems possible.…”
Section: Discussionmentioning
confidence: 99%